Deciphering ChatGPT`s Impact: Exploring Its Role in Cybercrime and Cybersecurity - Falade, Polra Victor (International Journal of Scientific Research in Computer Science and Engineering, 2024)
The advent of artificial intelligence (AI) technologies, exemplified by ChatGPT, has introduced profound implications for cybersecurity and cybercrime landscapes. This research employs a novel blog mining methodology to unravel the multifaceted roles of ChatGPT in these domains. Through comprehensive analysis of online discussions, articles, and expert insights, we elucidate how ChatGPT serves as a double-edged sword, enabling cybercriminal activities such as phishing, social engineering, and the generation of malicious content, while simultaneously offering potential solutions for enhancing cybersecurity defences. We provide a nuanced understanding of the intricate dynamics between ChatGPT and digital security, shedding light on emerging threats and opportunities. Our findings underscore the pressing need for proactive strategies to mitigate the risks posed by ChatGPT-driven cyber threats, while also harnessing its capabilities to bolster cybersecurity measures. This research aims to inform policymakers, cybersecurity professionals, and AI developers, guiding the formulation of effective policies and technologies to safeguard digital ecosystems in the face of evolving cyber threats.